Small Groups in a Social Learning MOOC (slMOOC): Strategies for Fostering Learning and Knowledge Creation - Krasny, Marianne; DuBois, Bryce; Adameit, Mechthild; Atiogbe, Ronnie; Baih, Lukman; Bold-erdene, Tergel; Golshani, Zahra; González-González, Rodrigo; Kimirei, Ishmael; Leung, Yamme; Shian-yun, Lo; Yao, Yue (Online Learning, 2018)
Social support and face-to-face learning may enhance outcomes for students who face barriers in accessing Massive Open Online Courses (MOOCs). In this study, we investigated how self-identified volunteer leaders guide and foster interactions among small groups of students who face technical and conceptual barriers in accessing MOOC content. Several months prior to the start of the MOOC (Environmental Education: Trans-disciplinary Approaches to Addressing Wicked Problems), we asked for volunteers among the registered students to lead groups for participants whose primary language was other than English and where limited Internet access, culture, or other barriers curtailed access to and understanding of course materials and pedagogy. Based on a survey and open-ended interviews (n=10), we found that group leaders were instrumental in overcoming barriers related to language, content, cultural ways of learning, access, and time. They also fostered cooperative learning strategies, which helped students acquire course content, and encouraged collaborative group projects leading to their groups adopting some features of online knowledge communities. We propose the term social learning MOOC (slMOOC) to capture a growing trend of incorporating collaborative learning strategies in xMOOCs.